Fingolimod protects against neurovascular unit injury in a rat model of focal cerebral ischemia/reperfusion injury - Xiao-Yu Zhu; Ting-Ting Ma; Yang Li; Ming-Qi Zhang; Liang Zhao; Jia Liang; Lian-Qiu Min (Neural Regeneration Research, 2023)
Recent research on the underlying mechanisms of cerebral ischemia indicates that the neurovascular unit can be used as a novel subject for general surveys of neuronal damage and protein mechanisms. Fingolimod (FTY-720) is a newly developed immunosuppressant isolated from Cordyceps sinensis that exhibits a wide range of biological activities, and has recently attracted much attention for the treatment of ischemic cerebrovascular diseases. In the current research, the role of FTY-720 and its possible mechanisms were assessed from an neurovascular unit perspective using a rat cerebral ischemia model. Our results revealed that FTY-720 markedly decreased infarct volume, promoted neurological function recovery, and weakened the blood-brain barrier permeability of ischemic rats. The protective roles of FTY-720 in ischemic stroke are ascribed to a combination of sphingosin-1-phosphate receptor-1 and reduced expression of sphingosin-1-phosphate receptor-1 in microvessels and reduction of interleukin-17A protein levels. These findings indicate that FTY-720 has promise as a new therapy for neurovascular protection and functional recovery after ischemic stroke.